Um exemplo de negação do conceito de elemento na filosofia natural - Cecon, Kleber [UNESP] (My University, 2013)
The focus of this work is to present an example of refutation of the concept of element inside the seventeenth-century scientific revolution, mainly through Robert Boyle’s The Sceptical Chymist. On the first section of this paper the notion of element as considered by the ancient Greeks in Aristotle’s Physics and modern chemists in Paracelsus will be briefly presented. After that in the second section Boyle’s deconstruction of the idea of element will be exposed considering his argumentation of why this notion is prejudicial to the study of nature. Finally, in the third section follows the constructive stage in which a new hypothesis is presented (the corpuscular hypothesis) as the best option to replace the notion of element.
Keywords: História da Ciência; História da Química; Robert Boyle